Economic Plants of Tripura State V. Pasture and Fodder - Deb, D. B. (Indian Forester, 1978)
The present paper entitled ’Economic Plants of Tripura State V. Pasture and fodder’ presents a study of pasture and fodder resources of Tripura State. An account of the development of grasslands is given. Plants used as pasture and fodder are named. Some suggestion for increasing the fodder resources are given.